Global geographies of innovation diffusion: the case of the Australian cattle industry - Tonts, M.; Yarwood, R.; Jones, Roy (Wiley-Blackwell, 2010)
The geographies and histories of the introduction of cattle breeds to Australia in the period since white settlement are documented as an example of the diffusion of agricultural innovations. Three phases of development are identified: a colonial expansion phase from the late eighteenth to the early twentieth century during which a number of primarily British cattle breeds were imported by the colonial settlers; an innovative phase in the mid twentieth century when both governments and private interests sought to produce or import new breeds deemed to be better adapted to Australian environments; and a multifunctional phase in recent decades. In this final phase, government deregulation and new technologies, such as the long distance transport of genetic packages, have facilitated the importation and development of many new cattle breeds in Australia.While this has produced a significant rise in the total number of breeds represented nationally, many recent and historic breeds currently exhibit extremely small numbers and a few generally well-established breeds such as Holstein, Hereford and Angus still dominate the national herd. This study of changing breed types and introductions provides some evidence of post-productivism and of a multifunctional transition in that several cattle breeds favoured by hobby farmers and boutique breeders are now represented, but the aggregate numbers for these breeds remain small and the numbers for several of the traditional (or colonial) breeds are currently in decline. Overall, it is apparent that Australia's cattle industry retains a strongly productivist ethos and that, particularly given the country's very great environmental variation, its levels of breed diversity remain low.